El grandioso altar de Pérgamo: Emblemática obra del mundo helenístico - Delgado Linacero, Cristina (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2002)
The great altar of Pergamo is one of the most important examples on the Hellenistic art, knowledge and thought. Erected by Eumenes II as a gratitude sign for gods help in the Gallic wars, this monument was part of the state propaganda and political and national exaltation. The selected subject for the outer frieze was the Gigantomachy myth or cosmogonic battle between gods and giants; the inner frieze told the story of Telephos, the legendary city founder. The present article deals with the meanings of this building, considered as one of the wonders from Antiquity.